Changes in Science Requirements in Earth Science Teacher Preparation Programs. - Mayer, Victor J. (Science Education)
The article discusses some of the changes made on the science requirements of the Earth Science teacher preparation programs. Included in the study's outline are the introduction of the study, the study design, the analysis and conclusions, the graph showing the comparison of the requirements in science disciplines for the year 1965 to 1969, the graph reflecting the percentage of the change in required course hours and the synopsis. The author also present the bibliography of the study for further reading.